URBAN GEOGRAPHICAL CHALLENGES AND MANAGEMENT (A study on Vizag City urban slums in Andhra Pradesh - INDIA) - challabathula, Dr.subha kumar; Useni, Pinjari; Rao, Prof. T. Koteswara (IJRDO - Journal of Social Science and Humanities Research, 2018)
Due to uncontrolled urbanization in India, environmental degradation has been occurring very rapidly and causing shortages of housing, worsening of water quality, excessive air pollution, noise, dust and heat, and the problems of disposal of solid wastes and hazardous wastes. The situation in metropolises like Mumbai, Kolkata, Chennai, Delhi and Bangalore, is becoming worse year by year.  As cities grow, so do their slum population. According to the Global Report on Human Settlements (United Nations Human Settlements Program, (2003) 924 million people in 2001 or almost 32 percent of the world's urban population lived in slums, the majority of them in the developing world. The proportion of the urban population living in slums is about seven times as high in less developed countries s (43 percent) and in more developed countries (6 percent)Globally, the slum population is set to grow at the rate of 27 million per year during the period 2000-2020. In response to these projections, the Millennium Development Goals established a target to significantly improve the lives of at least 100 million slum dwellers by the year 2020. In India, air pollution is proving to be an issue of concern. India's ongoing population explosion along with rapid urbanization and industrialization has placed significant pressure on its infrastructure and natural resources. According to reports, India's urban air quality ranks amongst the world are worst. Of the three million premature deaths in the world that occur each year due to outdoor and indoor air pollution, the highest numbers are assessed to occur in India. Some cities in India have witnessed decline in air pollution levels due to various measures taken by the Governments. In fact, according to a World Bank study, Delhi, Mumbai, Kolkata, Ahmadabad and Hyderabad have seen about 13,000 less premature deaths from air pollution related diseases. They represent the highest form of human degradation. They reflect the failure of our urban planners, municipal authorities and urban technology to provide basic services like water supply, toilets, drainage, and garbage disposal etc.   Due to unhealthy environmental conditions and Geographical settings of the vizag city urban slums in the Andhra Pradesh in India. Now India has recently committed to the development and construction of 100 Smart Cities to meet the demands of its rapidly growing and urbanizing population. In the state of Andhra Pradesh Visakhapatnam city selected as a smart city. In this research project analyzed some environmental challenges and issues for smart city concept.